2018
DOI: 10.14745/ccdr.v44i02a07
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Seoul virus among rats and rat owners — United States and Canada, 2017

Abstract: What is already known about this topic? Seoul virus, a type of hantavirus, is carried by Norway rats. Humans become infected through contact with virus shed in rat urine or droppings, or inhalation of virus particles in dust from contaminated bedding. Infected rats do not develop disease, but humans can experience symptoms ranging from mild influenza-like illness to severe disease with kidney failure and death. Although infections have been previously reported in humans after contact with wild rats, Seoul viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…However, mild and atypical clinical presentations are a constant feature of SEOV-induced HFRS forms, as repeatedly shown hereunder [1]. A family member later developed similar symptoms, but was not hospitalized [2]. In late December, 2016, a report of mild AKI followed in an 18-year-old female from Tennessee (USA) (hematuria and peak serum creatinine level of 1.27 mg/dL).…”
Section: Preludementioning
confidence: 63%
See 1 more Smart Citation
“…However, mild and atypical clinical presentations are a constant feature of SEOV-induced HFRS forms, as repeatedly shown hereunder [1]. A family member later developed similar symptoms, but was not hospitalized [2]. In late December, 2016, a report of mild AKI followed in an 18-year-old female from Tennessee (USA) (hematuria and peak serum creatinine level of 1.27 mg/dL).…”
Section: Preludementioning
confidence: 63%
“…A total of 24/183 (13.1%) US or Canadian residents associated with these facilities were found to be serologically SEOV-positive, resulting in three hospitalizations in the USA. No AKI was mentioned, and spontaneous recovery occurred, whereas no serious illness was reported from Canada [2]. Similar cases, with or without AKI, and all induced by apparently healthy pet rats, were described in the UK [5,6] and in France [7].…”
Section: Preludementioning
confidence: 86%
“…In 2008, the first locally acquired case of HFRS caused by the SEOV was confirmed. In 2017, the US CDC investigated an outbreak of SEOV infection that has infected 17 rat owners in seven states (Kerins et al, 2018). The number of hantavirus cases by year in different states is summarized in Figure 2.…”
Section: The Re-emergence Of Hantavirusmentioning
confidence: 99%
“…In Canada, HCPS is still very rare, but cases are recorded every year and show seasonal patterns, mainly between March and May and between September and November. A total of 64 cases have been confirmed since 2000, of which 12 were reported in 2013, most in western Canadian provinces such as Alberta, Manitoba, British Columbia, and Saskatchewan (Kerins et al, 2018). SNV and ANDV are responsible for the majority of hantavirus cases leading to HCPS.…”
Section: The Re-emergence Of Hantavirusmentioning
confidence: 99%
“…50 In 2017, outbreaks of SEOV infections occurred in several states of US. 51 This indicated that SEOV infections might be underdiagnosed, especially by the physicians outside of Asia. In the Netherlands, until very recently, a human case of SEOV infection has been reported.…”
mentioning
confidence: 99%